Combinations in the first-line treatment of patients with advanced/metastatic renal cell cancer: regulatory aspects. Issue 4 (26th August 2020) - Moscetti, Luca; Hennik, Paula; Bolstad, Bjorg; Camarero, Jorge; Josephson, Filip; Melchiorri, Daniela; Sommerfelt Grønvold, Maja; Sjoberg, Jan; Botezatu, Mihaela; Mulder, Jorn; Meulendijks, Didier; Trullas Jimeno, Ana; et al.
Abstract : The therapeutic landscape in the treatment of advanced/metastatic renal cell cancer has evolved over the last 2 years with the advent of immune checkpoint inhibitors. In 2018 and 2019, marketing authorisations valid throughout the European Union were issued for nivolumab and ipilimumab dual checkpoint inhibition and pembrolizumab or avelumab in combination with the tyrosine kinase inhibitor axitinib. These applications presented numerous regulatory challenges. In this paper, we summarise the main regulatory considerations, originating from the assessment of the dossiers submitted from the applicants for the three combinations. The regulatory issues are grouped in four sections: clinical pharmacology, efficacy, biomarkers and safety. In each section, we describe the issues raised during the regulatory evaluation performed by the Committee for Medicinal Products for Human Use (CHMP) assessors. The CHMP assessments determine whether the medicines concerned meet the necessary quality, safety and efficacy requirements, and whether the benefit–risk balance is positive. In summary, although the overall benefit–risk was considered positive for the three combinations, the immaturity of the outcome data and the absence of long-term safety data remain issues to be addressed. Postauthorisation efficacy studies have been required to confirm the effects of the new combinations.